2023
DOI: 10.1039/d2py01390h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermomechanical properties of sulfur-rich polymers by post-thermal treatment

Abstract: Recently, sulfur-rich polymers have been applied in various fields including energy storage, mercury absorption, and infrared (IR) optics. However, sulfur-rich polymers typically exhibit insufficient thermomechanical properties for practical applications. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…(h) Midwavelength IR (MWIR) and long-wavelength IR (LWIR) transmittance of SRP films with a thickness of 165 μm as a function of thermal treatment time at 110 °C. Images adapted with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Vacuum-assisted Thermal Treatment For Enhanced Thermo-mechan...mentioning
confidence: 99%
See 2 more Smart Citations
“…(h) Midwavelength IR (MWIR) and long-wavelength IR (LWIR) transmittance of SRP films with a thickness of 165 μm as a function of thermal treatment time at 110 °C. Images adapted with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Vacuum-assisted Thermal Treatment For Enhanced Thermo-mechan...mentioning
confidence: 99%
“…We first introduce a universal approach to enhance thermo-mechanical properties of SRPs, named vacuum-assisted thermal treatment. 36 Then, for value addition of SRPs, we will explain strategies to achieve a high-performance SRP-based IR polarizer, including the importance of high-fidelity in nanogratings as well as precise tailoring of spacer thickness on the performance of the polarizer. 22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among rare reports, J. Griebel found that in the inverse vulcanization of DIB, a too-long reaction time at high temperatures would lead to a flow transition of the polymer product, suggesting the breaking of the polymer network 29 . In contrast, D. Kim and his coworkers 30 discovered that the post-thermal treatment at 110 °C and 140 °C will improve the thermomechanical properties of inverse vulcanization products based on divinylbenzene in terms of glass transition temperature ( T g ) and storage modulus. C. Jenkins et al 31 investigated the effects of different reaction conditions, including reaction time, temperatures, scales, and feeding and heating procedures.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, only preliminary explanations were provided to elucidate the evolution of product structures and behaviors. The degradation of polysulfides at long reaction times was usually intuitively ascribed to the break and rearrangement of sulfur chains 28 , 30 . Moreover, most mechanism investigation and thermal treatment investigations were carried out with sole model monomer 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%